Return to sports, recreational activity and patient-reported outcomes after lateral unicompartmental knee arthroplasty - Walker, Tilman; Gotterbarm, Tobias; Bruckner, Thomas; Merle, Christian; Streit, Marcus R. (Knee surgery, sports traumatology, arthroscopy, 2015)
As the indication for unicompartmental knee arthroplasty (UKA) in recent years has been extended to young and more active patients, the expectations concerning the postoperative level of activity are high. The aim of the following study was to survey the activity level and the health-related quality of life of patients following lateral UKA.
Published online: 25 June 2014
Gesehen am 26.06.2020